2016
DOI: 10.1590/1089-6891v17i333327
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência De Eimeriose Em Bezerros Criados Em Propriedades De Agricultura Familiar - Nota Científica

Abstract: ResumoA ocorrência de eimeriose foi pesquisada em 110 bezerros da raça holandesa pertencentes a dez propriedades de agricultura familiar. As amostras de fezes foram coletadas via retal e analisadas por métodos parasitológicos qualitativos e quantitativos. Amostras de fezes positivas para Eimeria sp. foram submetidas à esporulação in vitro para posterior identificação microscópica da espécie. Todas as propriedades apresentaram positividade enteroparasitária por espécies do gênero Eimeria havendo uma prevalência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
8
4
Order By: Relevance
“…A similar study carried out two decades ago in the same region of the present work found that 16.69% of the animals were infected by Eimeria spp. (GUIMARÃES et al 1995), what it is much lower than the occurrence of 51.25% found in the present study, however, Hillesheim & Freitas (2016) whose worked at southwestern of Paraná, observed 48.2% of samples positives for Eimeria spp., this was very similar with prevalence of the present study. Eimeria alabamensis was found in 26.75% of the samples of the present study, and 9.1% in the work of Hillesheim & Freitas (2016), but was not described by Guimarães et al (1995).…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…A similar study carried out two decades ago in the same region of the present work found that 16.69% of the animals were infected by Eimeria spp. (GUIMARÃES et al 1995), what it is much lower than the occurrence of 51.25% found in the present study, however, Hillesheim & Freitas (2016) whose worked at southwestern of Paraná, observed 48.2% of samples positives for Eimeria spp., this was very similar with prevalence of the present study. Eimeria alabamensis was found in 26.75% of the samples of the present study, and 9.1% in the work of Hillesheim & Freitas (2016), but was not described by Guimarães et al (1995).…”
Section: Resultscontrasting
confidence: 71%
“…(GUIMARÃES et al 1995), what it is much lower than the occurrence of 51.25% found in the present study, however, Hillesheim & Freitas (2016) whose worked at southwestern of Paraná, observed 48.2% of samples positives for Eimeria spp., this was very similar with prevalence of the present study. Eimeria alabamensis was found in 26.75% of the samples of the present study, and 9.1% in the work of Hillesheim & Freitas (2016), but was not described by Guimarães et al (1995). These differences between our study and Guimarães et al (1995) work could be associate with the type of samples used, here feces samples were collected among animals without clinical signals, and the other one, most part of the animals (85.5%) had diarrhea.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…The diagnosis of the disease is based on clinical and epidemiological signs, in addition to a coproparasitological examination, in order to find fecal protozoan oocysts (HILLESHEIM & FREITAS, 2016).…”
Section: Introductionmentioning
confidence: 99%